Enhanced production of IL-18 in butyrate-treated intestinal epithelium by stimulation of the proximal promoter region - Kalina, Uwe; Koyama, Noriko; Hosoda, Tomoko; Nuernberger, Heike; Sato, Kazuto; Hoelzer, Dieter; Herweck, Frank; Manigold, Tobias; Singer, Manfred V.; Rossol, Siegbert; Böcker, Ulrich (European journal of immunology, 2002)
Expression of IL-18 in intestinal epithelial cells (IEC) has been implicated in Th1 cell-mediated chronic intestinal inflammation and anti-tumor immunity. However, physiological regulatory factors have not been identified. Besides their effects on proliferation and restitution, immunomodulatory functions have been attributed to short chain fatty acids (SCFA). We investigated the effect of SCFA (butyrate, propionate, acetate) on expression of IL-18 in IEC in vitro and in vivo. Expression of IL-18 mRNA and protein in human carcinoma-derived HT-29 and Caco-2 cells was analyzed by reverse transcription-PCR and Western blot. Transcriptional regulation of IL-18 gene expression was determined by transient transfection of wild-type and mutated IL-18 promoter. Further, in vivo expression of IL-18 in the intestine from butyrate-treated and untreated mice was assessed by immunohistochemistry. IL-18 mRNA and the IL-18 protein were expressed in IEC, while IL-18 secretion was not observed. Butyrate and acetate increased intracellular IL-18 content in a time- and dose-dependent fashion. In contrast to proinflammatory stimuli butyrate potently activated the IL-18 promoter, indicating that IL-18 is regulated at the transcriptional level by SCFA. Furthermore, a 108-bp sequence in the proximal region was identified to be essential for IL-18 promoter activation by butyrate. As proof of principle butyrate effects were confirmed in vivo by demonstration of increased IL-18 protein expression in IEC from butyrate-treated mice. In conclusion, SCFAup-regulate IL-18 protein expression in IEC, suggesting a potential regulatory contribution of these luminal constituents to T cell mediated inflammatory and neoplastic intestinal conditions.